Conversion of Cytochrome P450 2D6 of Human Into a FRET-Based Tool for Real-Time Monitoring of Ajmalicine in Living Cells - Ambrin, Ghazala; Ahmad, Mohammad; Alqarawi, Abdulaziz A.; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Ahmad, Altaf (Frontiers in Bioengineering and Biotechnology, 2019)
Ajmalicine is naturally present in the root bark of Catharanthus roseus L. and Rauvolfia serpentina (L.) Benth ex. Kurz. It has been extensively utilized in the treatment of hypertension across the world. The increased demand, overconsumption, and low content of the alkaloid in the plants have raised the issue of the depletion of natural sources. The metabolic engineering approach has not been successful in improving the content of the ajmalicine because the metabolic regulation of this metabolite is not known. The regulation of a metabolite in the metabolic pathway requires a tool that can carry out real-time measurement of the flux of the metabolite in living system. Given this, the present study was conducted to develop a genetically encoded FRET-based nanosensor by engineering human Cytochrome P450-2D6, an ajmalicine binding protein. The Cytochrome P450-2D6 was sandwiched between two FRET fluorophores. The design of the nanosensor brings two fluorescent proteins in conjunction with the ajmalicine binding protein, such that it undergoes FRET (Fluorescence Resonance Energy Transfer) upon binding of the ligand. The nanosensor, named as FLIP-Ajn (Fluorescence Indicator Protein for Ajmalicine), was pH stable and ajmalicine specific. The affinity of the FLIP-Ajn was 582 µM. The FLIP-Ajn successfully performed real-time measurement of ajmalicine in prokaryotic (bacteria) and eukaryotic systems (yeast, animal cell line and plant suspension culture), thereby, establishing its biocompatibility in monitoring of ajmalicine in living cells. Besides, several affinity mutants of the nanosensor were generated through mutations in the ajmalicine binding protein to increase the detection range of the nanosensor at varying physiological scales. The non-invasiveness and high spatial and temporal resolution of the tool holds a great significance in the bio-imaging of a highly compartmentalized metabolic pathway. The flux study of ajmalicine will help in identifying the regulatory steps involved in the synthesis of the alkaloids and, hence, will improve the production rate of ajmalicine from its natural sources.